Experiments and FE Analyses on Airborne Sound Properties of Composite Structural Insulated Panels - WAWRZYNOWICZ, Adam; KRZACZEK, Marek; TEJCHMAN, Jacek (Archives of Acoustics, 2014)
Airborne acoustic properties of composite structural insulated panels CSIPs composed of fibre-magnesium-cement facesheets and expanded polystyrene core were studied. The sound reduction ratings were measured experimentally in an acoustic test laboratory composed of two reverberation chambers. The numerical finite element (FEM) model of an acoustic laboratory available in ABAQUS was used and verified with experimental results. Steady-state and transient FE analyses were performed. The 2D and 3D modelling FE results were compared. Different panel core modifications were numerically tested in order to improve the airborne sound insulation of CSIPs.